Acute effect of pitching on range of motion, strength, and muscle architecture - Mirabito, N. S.; Topley, M.; Thomas, S. J. (The American Journal of Sports Medicine, 2022)
Background: Acute adaptations in clinical measures of range of motion and strength have been found after baseball pitching; however, there is a lack of research concerning the physiological mechanism responsible for these changes. Adaptations in muscle architecture of the infraspinatus and teres minor may serve as the structural changes responsible for these clinical measure changes.